Określenie wieku osobniczego na podstawie zębów - Otocki, Piotr (Polskie Towarzystwo Antropologiczne, 1988)
AGE DETERMINATION BASED ON TEETH. The set of dental traits traditionally used for identification purposes due to their high correlation with age include the attrition of the crown, periodontic changes, apposition of the secondary dentin and root cement, resorption and translueency of the root. The work puts forward a proposal to add a new trait, i. e. width of the root canal. The new trait is particularly useful for the examination of the fossil material/
AGE DETERMINATION BASED ON TEETH